2022
DOI: 10.1136/jitc-2022-005769
|View full text |Cite
|
Sign up to set email alerts
|

Activated NK cells reprogram MDSCs via NKG2D-NKG2DL and IFN-γ to modulate antitumor T-cell response after cryo-thermal therapy

Abstract: BackgroundMyeloid‐derived suppressor cells (MDSCs) can potently inhibit T-cell activity, promote growth and metastasis of tumor and contribute to resistance to immunotherapy. Targeting MDSCs to alleviate their protumor functions and immunosuppressive activities is intimately associated with cancer immunotherapy. Natural killer (NK) cells can engage in crosstalk with multiple myeloid cells to alter adaptive immune responses, triggering T-cell immunity. However, whether the NK-cell-MDSC interaction can modulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
0
16
1
Order By: Relevance
“…In addition, it has been shown that the interaction of NK cells with myeloid-derived suppressor cells (MDSCs) is involved in indirect mechanisms of T cell-NK cell crosstalk. Activated NK cells after cryo-thermal therapy reduced MDSCs accumulation via NKG2D-NKG2D ligands axis and reprogrammed MDSCs to a mature phenotype via IFN-γ, promoting CD4 Th1-dominant antitumour immunity in the B16F10 melanoma model [ 48 ]. Notably, evidence of bidirectional crosstalk between NK cells and T cells has emerged.…”
Section: Crosstalk Between Nk Cells and The Tmementioning
confidence: 99%
“…In addition, it has been shown that the interaction of NK cells with myeloid-derived suppressor cells (MDSCs) is involved in indirect mechanisms of T cell-NK cell crosstalk. Activated NK cells after cryo-thermal therapy reduced MDSCs accumulation via NKG2D-NKG2D ligands axis and reprogrammed MDSCs to a mature phenotype via IFN-γ, promoting CD4 Th1-dominant antitumour immunity in the B16F10 melanoma model [ 48 ]. Notably, evidence of bidirectional crosstalk between NK cells and T cells has emerged.…”
Section: Crosstalk Between Nk Cells and The Tmementioning
confidence: 99%
“…In recent years, NK cells are increasingly considered important for immunotherapy [ 11 , 65 ], impelling us to explore their role in predicting the immunotherapeutic response of ovarian cancer patients. Interactions between T cells and NK cells were widely reported [ 66 , 67 , 68 , 69 ], and two genes forming the prognostic risk model were found to participate in the regulating function of both T cells and NK cells, namely SLC11A1 [ 46 , 70 , 71 , 72 ] and EVL [ 51 , 73 , 74 , 75 ]. Thus, we infer that immunotherapeutic response might also be predicted by evaluating the functional state of NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that the predominance and persistence of CD4 + T cells could induce decade-long leukemia remission ( 34 ). Therefore, stimulating CD4 + T cells is crucial to achieving long-term antitumor immune memory in cancer immunotherapy ( 35 ). In this research, CD4 + memory T cells take up high contents in the tumor environment.…”
Section: Discussionmentioning
confidence: 99%